Photoelectrochemical Enhancement of Graphene@WS2 Nanosheets for Water Splitting Reaction - Mahmoud Nasr; Lamyae Benhamou; Ahmed Kotbi; Nitul S. Rajput; Andrea Campos; Abdel-Ilah Lahmar; Khalid Hoummada; Khaled Kaja; Mimoun El Marssi; Mustapha Jouiad (Nanomaterials, 2022)
Tungsten disulfide nanosheets were successfully prepared by one-step chemical vapor deposition using tungsten oxide and thiourea in an inert gas environment. The size of the obtained nanosheets was subsequently reduced down to below 20 nm in width and 150 nm in length using high-energy ball milling, followed by 0.5 and 1 wt% graphene loading. The corresponding vibrational and structural characterizations are consistent with the fabrication of a pure WS2 structure for neat sampling and the presence of the graphene characteristic vibration modes in graphene@WS2 compounds. Additional morphological and crystal structures were examined and confirmed by high-resolution electron microscopy. Subsequently, the investigations of the optical properties evidenced the high optical absorption (98%) and lower band gap (1.75 eV) for the graphene@WS2 compared to the other samples, with good band-edge alignment to water-splitting reaction. In addition, the photoelectrochemical measurements revealed that the graphene@WS2 (1 wt%) exhibits an excellent photocurrent density (95 μA/cm2 at 1.23 V bias) compared with RHE and higher applied bias potential efficiency under standard simulated solar illumination AM1.5G. Precisely, graphene@WS2 (1 wt%) exhibits 3.3 times higher performance compared to pristine WS2 and higher charge transfer ability, as measured by electrical impedance spectroscopy, suggesting its potential use as an efficient photoanode for hydrogen evolution reaction.